2001
DOI: 10.1055/s-0037-1615961
|View full text |Cite
|
Sign up to set email alerts
|

The mRNAs of Prekallikrein, Factors XI and XII, and Kininogen, Components of the Contact Phase Cascade Are Differentially Expressed in Multiple Non-hepatic Human Tissues

Abstract: SummaryRecently RT-PCR studies had demonstrated the expression of plasma prekallikrein (PPK) mRNA in extrahepatic tissues. The questions arose whether that is illegitimate or regular expression, and whether the mRNAs of blood coagulation factors XI and XII, and high molecular weight kininogen, components of the contact activation cascade of blood coagulation are also expressed in non-hepatic tissues. These questions were addressed in the present study by employing quantitative RT-PCR. The relative mRNA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Although hepatocytes were considered to synthesise plasma prekallikrein and PPK mRNA expression was highest in the liver (Neth et al, 2001), direct evidence of its presence in the liver was obtained only when the enzyme was demonstrated in isolated hepatocytes by immunofluorescence (Henderson et al, 1992). In the current study, we confirmed the localisation of PPK/PK in human hepatocytes ( Figure 3A).…”
Section: Liversupporting
confidence: 77%
See 3 more Smart Citations
“…Although hepatocytes were considered to synthesise plasma prekallikrein and PPK mRNA expression was highest in the liver (Neth et al, 2001), direct evidence of its presence in the liver was obtained only when the enzyme was demonstrated in isolated hepatocytes by immunofluorescence (Henderson et al, 1992). In the current study, we confirmed the localisation of PPK/PK in human hepatocytes ( Figure 3A).…”
Section: Liversupporting
confidence: 77%
“…With 0.3% compared to liver, mRNA expression in lung was very low (Neth et al, 2001). Nevertheless, as in the epithelium of other glandular organs, epithelial cells forming the respiratory epithelium stained positively for PPK/PK.…”
Section: Respiratory Tractmentioning
confidence: 91%
See 2 more Smart Citations
“…These include secreted enzymes, such as trypsin I, II (Paju et al, 2000;Bjartell et al, 2005) and IV (Takeuchi et al, 1999;Cottrell et al, 2004); other more complex secreted serine proteinases, containing modular nonproteolytic domains, such as factor XIIa (Takeuchi et al, 1999), plasma kallikrein (Neth et al, 2001;Fink et al, 2007), urokinase (also known as urinary plasminogen activator, uPA; Gavrilov et al, 2001;Riddick et al, 2005;Usher et al, 2005) and protein C (He et al, 1995;Takeuchi et al, 1999); the multi-serine proteinase domain containing enzymes polyserase-2 and -3 (Cal et al, 2005(Cal et al, , 2006; the glycosyl-phosphatidylinositol membraneanchored serine proteinase prostasin (Chen et al, 2001); as well as nine members of the type II transmembrane serine proteinase (TTSP) sub-family (Hooper et al, 2001;Netzel-Arnett et al, 2003) including hepsin, enteropeptidase (Cottrell et al, 2004), matriptase/MT-SP1 (Saleem et al, 2006), TMPRSS2 (Lin et al, 1999), TMPRSS3 (Scott et al, 2001), TMPRSS13 (Kim et al, 2001), human airway trypsin-like proteinase (HAT) (Hahner et al, 2005), DESC1 (Lang and Schuller, 2001) and the multi-catalytic domain TTSP polyserase-1 (Okumura et al, 2006). It is also interesting to note the co-expression in prostatederived cell lines of trypsinogen I, II and IV and the in vivo Brought to you by | University of Queensland -UQ Library Authenticated Download Date | 9/14/15 3:38 AM activator of these enzymes, the TTSP enteropeptidase (Light and Janska, 1989;Kitamoto et al, 1994).…”
Section: Par Cleavage By Other Prostatic Trypsin-like Serine Proteinasesmentioning
confidence: 99%